DataSheet1_Tidal impacts on air-sea CO2 exchange on the North-West European shelf.docx - Jan Kossack; Moritz Mathis; Ute Daewel; Feifei Liu; Kubilay Timur Demir; Helmuth Thomas; Corinna Schrum (2024)
Tidal forcing is a dominant physical forcing mechanism on the Northwest European Shelf (NWES) that regulates the mixing-stratification status of the water column and thus acts as a major control for biological productivity and air-sea CO 2 exchange. Tides further influence the marine carbon cycle on the shelf by affecting benthic-pelagic coupling, vertical mixing and the large-scale residual circulation. The cumulative tidal impact on oceanic uptake of atmospheric CO 2 on the NWES, however, remains largely unexplored. We use a coupled physical-biogeochemical ocean model to gain quantitative understanding of the tidal impacts on the air-sea CO 2 exchange of the NWES by comparing hindcast simulations with and without tidal forcing. Our results show that tidal forcing weakens the annual oceanic CO 2 uptake on the NWES by 0.15 Tmol C yr−1, corresponding to a ~13% stronger CO 2 sink in the experiment without tidal forcing. The tide-induced increase in marine primary production demonstrated in earlier studies, which primarily enhances biological carbon fixation in shallow inner-shelf regions of the NWES, does not significantly affect net air-sea CO 2 exchange. Instead, we find tidal mixing, tide-induced baroclinic circulation and the tidal impact on benthic-pelagic coupling to be dominant controls of air-sea CO 2 exchange. Tidal mixing in the permanently mixed shelf regions accounts for the majority (~40%) of the weakening effect on CO 2 uptake, while the modulation of water mass composition in the Celtic Sea by tide-induced baroclinic circulation reduces the uptake further (~33% of the difference in annual mean CO 2 uptake). In terms of the shelf carbon budget, the tidal response of air-sea CO 2 exchange is primarily mediated by changes to the pelagic DIC reservoir (~73%; −0.11 Tmol C yr−1). Tidal impacts on off-shelf carbon export to the North Atlantic only account for ~20% (−0.03 Tmol C yr−1) of the tidal impact on shelf CO 2 uptake, and changes in sedimentation of particulate organic carbon account for the ...